Use of Modern Pedagogical Technologies in Teaching Mathematics in Schools - Sunnatullo Do’stov; Ruxshona Egamberdiyeva (Genius Journals, 2023)
This article describes in detail the purpose of using modern pedagogical technologies in the teaching of mathematics in schools, expanding the field of application of computer technologies, organizing students' educational work, stimulating their activities, and using modeling programs.
Keywords: modern pedagogical technologies; mathematical problem; spreadsheets; function